DAMPAK PENGHENTIAN PERKARA TERHADAP TERSANGKA MELALUI PRAPERADILAN DALAM PROSES PENYIDIKAN TINDAK PIDANA PERPAJAKAN - Suyadi (2021)
There are various criminal acts or criminal acts or tax violations that can be subject to criminal sanctions. With the publication of the Criminal Procedure Code, abbreviated as KUHAP, a pretrial isformed which is tasked with maintaining order in the investigation and protecting the suspect against the actions of investigators and public prosecutors that violate the law and harm the suspect. The purpose of this research is to find out and normatively review the pre-trial institution having the authority to examine and adjudicate the application to terminate the investigation submitted by the suspect and to find out juridical considerations as the basis for the petition for the pretrial authority case against the request for termination of investigation submitted by the suspect. This research is a normative juridical research. The conclusion is obtained that pretrial is the authority of the district court to examine and decide according to the method regulated in this law, regarding whether an arrest is legal or not and / or at the request of the suspect or his family or other party on the power of the suspect, whether or not the termination of investigation or prosecution is legal. on requests for the sake of upholding law and justice and based on Article 50 of the Criminal Procedure Code and Article 4 paragraph (2) of Law No 48 of 2009 concerning Judicial Power, Article 50 of the Criminal Procedure Code and Article 4 paragraph (2) concerning Judicial Power give the suspect or defendant the right to his fate is not in limbo and has legal certainty.